Differentiated block method of analysis and forecasting indicators of power consumption of the industrial complex - IU Rakhmonov, T H Khakimov, II Bakhadirov, B M Khusanov (International Journal of Advanced Science and Technology, 2020)
Determining a more accurate forecast value of electricity consumption for industrial enterprises is an important factor in the rational use of electric energy. For this purpose, the authors propose the method of forecasting the electric power consumption using the differentiated block method of analysis and forecasting of the electric power consumption indicators of the industrial complex. The method has several advantages with comparison of the existing ones. The main advantage is that all main and auxiliary factors influencing the electric power consumption are taken into account when determining the predicted value of electric power consumption.